An Analysis of Aboriginal Employment: 2009–2013 - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2014)
The employment, unemployment and participation rates are examined for Aboriginals living off-reserve in Canada from 2009 to 2013 as well as for non-Aboriginals. Employment is analyzed by educational level, gender and age, province and territory and by industry and sector. The rates of employment and unemployment for Aboriginals have continued to improve, lessening the differences with non-Aboriginals. Those in the 15 to 24 age group and women had the largest improvements in their employment and unemployment rates in 2013. The level of education obtained is directly related to the rate of employment for Aboriginals and non-Aboriginals and explains most of the difference in their rate of employment, but does not explain the differences in unemployment rates. The highest rate of employment for Aboriginals and non-Aboriginals is in Alberta. The areas in which the highest percent of those employed are in health care and social assistance followed by retail trade.